The Role of Infertility Stress and Defeat in Predicting the Quality of Infertile Women\'s Marital Relationship - Seyedeh Mohadeseh Rezaei (Qom University of Medical Sciences, 2021)
Background and Objectives: Infertility is one of the bitter experiences of life that causes many psychological problems for the individual and his family. The aim of this study was to investigate the role of infertility stress and defeat in predicting the quality of infertile womenchr(chr(chr(chr('39')39chr('39'))39chr(chr('39')39chr('39')))39chr(chr(chr('39')39chr('39'))39chr(chr('39')39chr('39'))))s marital relationship. Methods: The present study was a descriptive correlational study. A sample of 120 infertile women using the available sampling method was selected from women who referred to the Infertility Center in Birjand in 2020. Research tools included Newton et al.chr(chr(chr(chr('39')39chr('39'))39chr(chr('39')39chr('39')))39chr(chr(chr('39')39chr('39'))39chr(chr('39')39chr('39'))))s infertility stress scale, Gilbert and Allenchr(chr(chr(chr('39')39chr('39'))39chr(chr('39')39chr('39')))39chr(chr(chr('39')39chr('39'))39chr(chr('39')39chr('39'))))s sense of failure, and the quality of the right marriage relationship with colleagues. To analyze the data, Pearson correlation coefficient and multiple regressions were used simultaneously using SPSS software version 22 at a significance level of 0.05. Results: The results showed that there was a direct relationship between infertility stress (r = 0.722) and feelings of failure (r = 0.651) and the quality of marital relationship (p <0.01). Also, the value of standardized regression coefficient (Beta) for infertility stress components including social dimension (p = 0.014, β = 0.135), sexual dimension (p = 0.035, β = 0.88), communication (p = 0.166, β = 0.260), lifestyle non-acceptance (p <0.001, β = 0.235), need for parenting (p <0.001, β = 0.219) and failure feeling component Included feelings of stagnation (p <0.001, β = 0.240), feeling of loss (p <0.001, β = 0.225) and feelings of satisfaction (p <0.001, β = 0.261). Conclusion: Based on the results of the study, it can be said that with increasing infertility stress and feelings of failure, the quality of the marital relationship of infertile women decreases. Thus, infertility stress and feelings of failure play a crucial role in the quality of infertile womenchr(chr(chr(chr('39')39chr('39'))39chr(chr('39')39chr('39')))39chr(chr(chr('39')39chr('39'))39chr(chr('39')39chr('39'))))s marital relationship.